Thermal Degradation and Structural Characteristics of Corn Stover After Ferric Chloride Solution Pretreatment - Zeng, G.M.; Wang, Y.L.; Zhang, M.L.; Zheng, Y.X.; Xing, J.; Ma, Y.F.; Xu, H.J. (Asian Journal of Chemistry, 2012)
Thermal properties of the corn stover cellulose and these ingredients were examined by thermogravimetric analysis under dynamic conditions from ambient to 800 ºC, in order to predict the thermal behaviour of the corn stover cellulose after ferric chloride solution pretreatment. Thermogravimetric analyses were performed at heating rates of 10, 20 and 30 ºC/min-1 in nitrogen atmospheres. The parameters of the reaction kinetics were calculated following the Ozawa-Flynn-Wall (OFW) method and compared with untreated corn stover. Using non-isothermal conditions, average value of the reaction activation energy was determined to and 153.77 and 141.88 KJ/mol for the untreated and treated corn stover. Structure of corn stover was heavily damaged by ferric chloride solution pretreatment compared with untreated corn stover, as characterized by X-ray diffraction and scanning electron microscopy. Fourier transform infrared analysis indicated that ferric chloride solution pretreatment could easily remove the hemicelluloses.